Rosmarinic Acid from Orthosiphon aristatus Potentially Targets Estrogen Receptor-Alpha in Breast Cancer: In-silico Study - Qurrotaayun, Ghina Alya Putri; Sitompul, Joy Elizabeth Nauli; Fadhilah, Naya; Pramudita, Fransisca Widi; Putri, Nazwa Septiriana; Muljono, Fajar Oktavian; Fardhan, Firghi Muhammad; Novitasari, Dhania (Indonesian Society for Cancer Chemoprevention, 2024)
Breast cancer is the most common cancer among women. Tamoxifen, a widely used estrogen receptor-alpha (ER-α) inhibitor, is effective but often causes side effects, necessitating the search for alternative inhibitors from natural sources. Ortosiphon aristatus, also known as cat's whiskers, is a medicinal plant traditionally valued for its anti-inflammatory and antioxidant properties. Recent studies suggest its bioactive compounds may exhibit anticancer activity by inducing apoptosis in cancer cell lines. This study explores the potential of O. aristatus metabolites as ER-α inhibitors using computational approaches. Nine metabolites were assessed for their physicochemical properties based on Lipinski’s rule of five and ADMET predictions, followed by pharmacophore-based virtual screening with LigandScout and molecular docking with AutoDock. The results showed that all tested compounds complied with Lipinski’s rule, and most met ADMET criteria. Among these, rosmarinic acid was identified as one of the hit compounds based on pharmacophore screening, exhibiting binding interactions comparable to 4-hydroxytamoxifen with the ER-α amino acid residues HIS524 and GLY521. It also demonstrated a binding energy of -8.02 kcal/mol and a low inhibition constant (Ki) of 1.31 μM. These findings highlight the potential of O. aristatus and rosmarinic acid for further evaluation as candidates against ER-α in breast cancer cells.Keywords: breast cancer, estrogen receptor-alpha, Orthosiphon aristatus, in silico.